New species of the asteroid genus Haccourtaster Jagt, 2000 (Echinodermata, Goniasteridae) from the Upper Cretaceous of Denmark, Sweden and the United Kingdom - Gale, Andrew S.; Jagt, John W. M. (Zootaxa, 2025)
Three new species of the small Late Cretaceous goniasterid genus Haccourtaster are described, viz. H. berryensis sp. nov. from the lower Turonian of Devon (UK), H. nattestadae sp. nov. from the lower Coniacian of Bornholm (Denmark) and H. liticola sp. nov. from the lower Campanian of Ivö Klack (southern Sweden). Species are differentiated on surface sculpture of the marginal ossicles. Members of this genus evidently preferred high-energy, nearshore environments, but are also found, albeit less commonly, in deeper-water chalk facies.